2022
DOI: 10.1021/acs.jpcb.2c05584
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics of mCherry Variants: A Link between Side-Chain Motions and Fluorescence Brightness

Abstract: The 3-fold higher brightness of the recently developed mCherry-XL red fluorescent protein (FP) compared to its progenitor, mCherry, is due to a significant decrease in the nonradiative decay rate underlying its increased fluorescence quantum yield. To examine the structural and dynamic role of the four mutations that distinguish the two FPs and closely related variants, we employed microsecond time scale, all-atom molecular dynamics simulations. The simulations revealed that the I197R mutation leads to the for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Mukherjee et al also observed two states of the gap, albeit with slightly different populations than those observed here. 61 This difference in state populations may be due to differences in force field choice, simulation system, or conformational sampling (i.e., 2 µs vs. 20 µs in the present work).…”
Section: Peg Influences Local Structure In the Ordered Region Of Mcherrymentioning
confidence: 89%
See 2 more Smart Citations
“…Mukherjee et al also observed two states of the gap, albeit with slightly different populations than those observed here. 61 This difference in state populations may be due to differences in force field choice, simulation system, or conformational sampling (i.e., 2 µs vs. 20 µs in the present work).…”
Section: Peg Influences Local Structure In the Ordered Region Of Mcherrymentioning
confidence: 89%
“…This gap is a vestige of the missing tetrameric interactions disrupted by mutations introduced to design a monomeric FP. 85 Previous studies have shown that the β7-β10 gap undergoes structural transitions between closed and open states, 61 allowing molecular oxygen to diffuse into the barrel and affect the photostability of the chromophore. 55,85 To determine the width of the β7-β10 gap, we measured the distance between three residues on β7 (E144, A145, S146) and three residues on β10 (I197, K198, L199).…”
Section: Peg Influences Local Structure In the Ordered Region Of Mcherrymentioning
confidence: 99%
See 1 more Smart Citation
“…We performed all-atom molecular dynamics simulations, spanning approximately 500 ns, 31 to evaluate the influence of single substitutions at positions 175, 42, 159, and 218 in FR. (SI Section S2b-e).…”
Section: Simulationsmentioning
confidence: 99%
“…MD Simulations. We performed all-atom molecular dynamics simulations, spanning 500 ns, 31 to evaluate the influence of single substitutions at positions 175, 42, 159, and 218 in FR (Supporting Information Section S2). Computational details are provided in Supporting Information Section S1e.…”
mentioning
confidence: 99%